Efektivitas Program Back School Dan Teknik Mckenzie Pada Pasien Nyeri Punggung Bawah - Saifudin Zuhri; Marti Rustanti (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Back School Program, Mckenzie Techniques, Pain, Vas, Patients With Low Back Pain. Low back pain is a problem that affects about 60-80% of the population in his lifetime. This pain is often triggered behavior ergonomics so that the necessary education in school programs to lower back pain. On the other hand needed McKenzie method for relaxation to the muscles of the back due to spasm, so that the pain can be reduced. Objective: To prove the effectiveness of the program back school and McKenzie techniques in reducing lower back pain. Types of Research: an experimental study. The study design: two group pre-test-post-test design. Statistical Analysis: The subjects in one group <30 people, then analyzed with nonparametric tests. Homogeneity of data was tested with the Mann-Whitney test was obtained p = 0.030 (P <0.05) indicates the data are not homogeneous. Wilcoxon test group I obtained p = 0.000 (p <0.05) showed no differential effect of back school programs to decrease lower back pain. Wilcoxon test group II obtained p = 0.000 (p <0.05) showed no differential effect of McKenzie technique to decrease lower back pain. Mann-Whitney test after treatment was obtained p = 0.006 (p <0.05) showed no difference in effectiveness between the back school program with McKenzie techniques in reducing lower back pain. Results of the mean difference in pain reduction anatara back school program with the technique gained 9.71 higher McKenzie McKenzie techniques. Conclusion: McKenzie technique is more effective than a back school program to reduce lower back pain